Ciclovias e ciclofaixas em Cuiabá e Várzea Grande : representação visual, tensões culturais e perspectivas na comunicação - Brandão, Maria Luiza Queiroz (2020)
The research search for identifies the bike lanes and bike lanes built in the municipalities of Cuiabá and Várzea Grande, in Mato Grosso, considering the characteristics of the road structure of an urban agglomerate originating in the 18th century. The construction of bike lanes and bike lanes presents cultural tensions related to traffic, which is dominated by automobiles, and also communication perspectives, about ways of representing and thinking about the presence of cyclists in the confusing daily life of cities. A major problem is that bike paths are not always built with quality, safety, and in an integrated way with each other and with public transport. They are often disconnected from the areas of consumption, work, education, leisure, and service goods. In Greater Cuiabá, the site of this research, the culture of bicycles still resists. The central question was to analyze whether the network system of bike lanes and bike lanes is represented as a public communicational space. The specific objectives defined were: a) to map the bike lanes and bike lanes; b) present a conceptual typology, according to Brazilian standards; c) register the main communication problems (signaling) and cultural issues (conflicts between cyclists and other traffic subjects: mainly drivers and pedestrians). In a technical instance, we seek to develop representations of bike lanes and bike lanes in two descriptive modes: graphic representations, based on information for official maps of the municipalities, and photographic records, aiming to produce a set of images about structural and functional conditions of bike lanes and bike lanes. In a methodological instance, it starts from the theoretical model of communication as culture in a qualitative and descriptive research, based on field observation. The bike lanes, when implanted, gain prominence and inviting contours for cycling practice, which, when allowed, pedestrians are allowed to enjoy these shared spaces. Emerging social practices are also addressed, dialogue in the field of communication and culture.